Relative risk of COVID-19 pandemic and regional inflation convergence in Indonesia: Spatial panel data approach - Sayifullah, Sayifullah; Arifin, Samsul (Optimum: Jurnal Ekonomi dan Pembangunan, 2024)
The purpose of this study is to investigate the relationship between the risk of a COVID-19 pandemic and regional inflation convergence in Indonesia. Because the COVID-19 recession differs from the previous inflation recession, it is important to investigate regional inflation convergences in order to evaluate the inflation rate and the impact of macroeconomic policy on inflation convergence. The spatial panel data used in this study ranges from 2020:M3 to 2021:M12. The dynamic econometric spatial panel data model is used to quantify relative risk without spatial or SIRs to calculate the impact of the COVID-19 pandemic on regional inflation convergence in Indonesia. On the contrary, for calculating the risk relative to spatial elements, the CAR Leroux or BSCL Bayesian Spatial Model is used. Using BSCL, the calculation of the relative risk value for the COVID-19 pandemic concludes that Sumatera Island, Java Island, Kalimantan Island, Sulawesi Island, Maluku Island, and Papua Island have high risks, while Bali Island and Nusa Tenggara Island have low risks. In both static and dynamic models, the influence of currency circulation on inflation convergence is positive, and the relative risk of a COVID-19 pandemic on inflation convergence is negative. Monetary phenomena during the COVID-19 pandemic determined inflation behavior in Indonesia. Studies show that the COVID-19 pandemic is a deterrent to inflation convergence, while the circulation of money drives inflation convergence.